Vapour pressures and osmotic coefficients of binary mixtures of 1-ethyl-3-methylimidazolium ethylsulfate with alcohols at 323.15 K - Noelia Calvar (2009)
Osmotic coefficients of binary mixtures containing alcohols (ethanol, 1-propanol, 2-propanol) and the ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate weredetermined at 323.15 K. Vapour pressure and activity coefficients of the studiedsystems were calculated from experimental data. The extended Pitzer modelmodified by Archer, and the modified NRTL model (MNRTL) were used to correlatethe experimental data, obtaining standard deviations lower than 0.012 and 0.031,respectively. The mean molal activity coefficients and the excess Gibbs free energyof the studied binary mixtures were calculated from the parameters obtained with theextended Pitzer model of Archer.